Результати дослідження диспергування гетерогенних матеріалів у спіральному нагрівальному елементі термовакуумної установки - Кутовий, В. О. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2025)
The paper considers physical processes in a thermal – vacuum installation that allow for the effective dispersion of heterogeneous materials. The analysis of heat and mass transfer processes affecting the dispersion of heterogeneous materials carried out. The calculations of the velocity, frequency and wavelength in spiral heating element of the thermal – vacuum installation for different angles of movement of material particles performed. It established that the velocity of movement of the material part in the cavity of the heating element be more than a thousand kilometers per second, and the temperature of the local pulsed steam explosion increases to tens of millions of degrees. At such a temperature, local thermonuclear fusion may occur, as result of which hydrogen converted into helium. The results of the study show that during thermal – vacuum dispersion of heterogeneous materials, modified nanodispersed materials formed, neutrinos and transparent bubbles appear. All these transformations occur in spiral heating element of the thermal – vacuum installation within 15 s.